Modern India's pioneer economic adviser - Chandavarkar, Anand (2007)
India is the unique domain of the economic adviser, which goes back to the legendary Kautilya, minister to Chandragupta Maurya. The pioneer economic adviser of modern India, however, was a little known American economist Ralph Whitenack, who served with distinction the Gaekwar of Baroda, Sayajirao III during 1906-09 and 1918-19 and was the prime architect of the Bank of Baroda. This article reviews his work in Baroda and its contemporary lessons. - Reproduced.
Keywords: Economics